Type 2 Diabetes Patients' Perspectives, Experiences, and Barriers Toward Diabetes-Related Self-Care: A Qualitative Study From Pakistan - Bukhsh, Allah; Goh, Bey-Hing; Zimbudzi, Edward; Lo, Clement; Zoungas, Sophia; Chan, Kok-Gan; Khan, Tahir Mehmood (Frontiers in Endocrinology, 2020)
Objective This study aimed to qualitatively explore perspectives, practices, and barriers to self-care practices in Urban Pakistani adults with type 2 diabetes mellitus (T2DM). Methods Pakistani adults with T2DM were recruited from the outpatient departments of two hospitals in Lahore. Semi-structured interviews were conducted and audio-recorded until thematic saturation was reached. Two researchers thematically analyzed the data independently using NVivo® software with differences resolved by a third researcher. Results Thirty-two Pakistani adults (aged 35-75 years, 62% female) participated in the study. Six themes were identified from qualitative analysis: role of family and friends; role of doctors and health-care; patients’ understanding about diabetes; complication of diabetes and other co-morbidities; burden of self-care; and, life circumstances. A variable experience was observed with education and healthcare. Counseling by healthcare providers, family support and fear of diabetes-associated complications, were the key enablers that encouraged the study participants to adhere to diabetes-related self-care practices. Major barriers to self-care were: financial constraints, physical limitations, extreme weather conditions, social gatherings, food loving-nature, forgetfulness, needle phobia, and, hectic job nature. Conclusion Respondents identified many barriers to diabetes self-care, particularly related to life situations and diabetes knowledge. Family support and education by healthcare providers were key influencers to self-care practices among Pakistani people with diabetes.